Discovering Appropriate Policy to Strengthen Indonesia’s Space Science: A Discourse Network Analysis - Zaki, Ahmad; Alamsyah, Purnama; Pratomo, Adhi; Triwahyuni, Desi (National Research and Innovation Agency, Indonesia, 2025)
Changes in institutional structures, mandates stated in laws and regulations, growing community participation, and the involvement of government institutions in international space organizations have resulted in issues related to countries’ contribution of roles and responsibilities, as well as the strategic value of collaboration for implementing national space science. This study presents the discourse on space science activities in Indonesia. Based on the analysis results of 92 online media articles published from 2022 to 2024, various actors spoke about space science, emphasizing more collaboration and a formulary of technical regulations to handle the country’s wide area, while considering modalities that need to be strengthened and challenges that need to be addressed. Using a relationship mapping method known as discourse network analysis (DNA), in which the results were analyzed for causal-effect among them, this study has identified three gaps as the national priority needs: space security for national sovereignty, space disaster mitigation due to falling space objects, and flight safety due to space weather. This study has explained these challenges through a framework that captures the interplay of actors, policy gaps, specific sophisticated technologies, and mandates of actors.